ANALYSIS OF THE CHARACTERIZATION IN “ITAEWON CLASS” KOREAN DRAMA - Oktaviani, Betsi; Cholifah, Maria; Lutviana, Rizky; Sriwulandari, Novi (HUMANIS: Jurnal Ilmu-Ilmu Sosial dan Humaniora, 2024)
This research is aimed at analyzing the characterizations of the five main characters in “Itaewon Class” korean drama. The analysis of the characterization includes the appearance of the characters, the personality of the characters, the social status of the characters, and the social relationship of the characters. The object of this research is the four main characters, namely Park Sae Ro-Yi, Jo Yi-Seo, Oh Soo-Ah, and Jang Dae-Hee This research applied descriptive qualitative research design. Data collection process includes: (1) watching the “Itaewon Class” drama, (2) reading the story of “Itaewon Class” and (3) preparing theory regarding the character and characterization. The findings of this research are each character has different characters. Park Sae Ro-Yi is known as a high integrity, hard-working, responsible, care, and never gives up man. He is also known as a man who has a good attitude. Jo Yi-Seo is described as a girl who has some characters, such as sociopath, lack of empathy, smart and full of charm, discipline, and confident. Oh Soo-Ah grows up as a realistic, consistent, firm, hard-working, not easily to give up and disciplined woman. Jang Dae-Hee is well-known as a rough, wicked, hard-working, cunning, vengeful, and caring man.